In Hospital Outcomes in Patients with Non-ST Elevated Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Raza, Mahzaib; Bari, Abdul Manan; Saleem, Qaiser; Ijaz ul Haq,; Ajmal, Laiba (Indus Journal of Bioscience Research, 2024)
Objective: To evaluate the in-hospital outcomes of patients with non-ST elevated myocardial infarction (NSTEMI) undergoing percutaneous coronary intervention (PCI).Methodology: A total of 200 NSTEMI patients who underwent PCI were included in this prospective observational study. The study was conducted in the Department of Cardiology, Pakistan Atomic Energy Commission (PAEC) General Hospital, Islamabad, Pakistan, from January to June 2024.Patient demographics, clinical characteristics, and procedural outcomes were analyzed. The primary endpoints were the success rate of PCI and in-hospital mortality. Secondary measures included door-to-balloon time and the relationship between comorbidities such as hypertension and diabetes. Data were analyzed using chi-squared tests and descriptive statistics.Results: The PCI success rate was 87.5%, with 12.5% of patients experiencing complications. The in-hospital mortality rate was 4.5%. The mean door-to-balloon time was 82.33 ± 9.93 minutes, with no significant difference between successful and complicated procedures. The chi-squared test revealed no statistically significant association between hypertension and diabetes (p = 0.4167). The results demonstrate that PCI for NSTEMI patients at this facility is highly effective and comparable to international outcomes.Conclusion: PCI is a successful and life-saving intervention for NSTEMI patients, with a high procedural success rate and low in-hospital mortality. This study provides essential data for NSTEMI management in Pakistan, filling a gap in local literature and supporting timely PCI as a standard of care to improve patient outcomes.